The architects of international relations building a discipline, designing the world, 1914-1940 - Stöckmann, Jan 1989- (Cambridge University Press, 2022)
Based on extensive archival research, this book provides a new and stimulating history of International Relations (IR) as an academic discipline. Contrary to traditional accounts, it argues that IR was not invented by Anglo-American men after the First World War. Nor was it divided into neat theoretical camps. To appreciate the twists and turns of early IR scholarship, the book follows a diverse group of men and women from across Europe and beyond who pioneered the field since 1914. Like architects, they built a set of institutions (university departments, journals, libraries, etc.) but they also designed plans for a new world order (draft treaties, petitions, political commentary, etc.). To achieve these goals, they interacted closely with the League of Nations and its bodies for intellectual cooperation, until the Second World War put an end to their endeavour. Their story raises broader questions about the status of IR well beyond the inter-war period